Adolescent Dating Violence Victimization and Relationship Dissolution. Issue 2 (March 2020) - Soller, Brian; Copp, Jennifer E.; Haynie, Dana L.; Kuhlemeier, Alena
We integrate literature on gender and adolescent friendships to examine the association between adolescent dating violence victimization (ADVV) and relationship dissolution. In particular, we test whether ADVV increases the hazard of relationship dissolution among adolescent romances, and whether a number of friendship dynamics alter the association between ADVV and relationship dissolution. Using discrete time event history models from 5, 787 romantically involved youth from the National Longitudinal Study of Adolescent to Adult Health (Add Health), results indicated, on average, ADVV was not associated with the hazard of relationship dissolution for girls or boys. However, the positive effect of ADVV was stronger for girls who did not withdraw from their friendships over the course of their romantic relationships. This study highlights the importance of peer groups and gender in shaping youths' decisions to exit abusive relationships.